2014
DOI: 10.1016/j.applthermaleng.2013.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of methods to reduce the energy consumption of food cold stores

Abstract: Energy is a major cost in the operation of food cold stores. Work has shown that considerable energy savings can be achieved in cold stores. Results from 38 cold store audits carried out across Europe are presented.\ud \ud Substantial savings could be achieved if operation of cold storage facilities were optimised in terms of heat loads on the rooms and the operation of the refrigeration system. Many improvements identified were low in cost (improved door protection, defrost optimisation, control settings and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(39 citation statements)
references
References 4 publications
0
39
0
Order By: Relevance
“…Another piece of relevant information was the number of workers going through cold stores. The insulation and the number of workers are the important variables in the balance of energy and the thermal load calculation (Evans et al, 2014;He et al, 2014;Johnston, 1994). Failure to observe these characteristics compromises the proper functioning of the equipment, causes excessive consumption of energy and compromises the quality of seafood (Johnston, 1994).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another piece of relevant information was the number of workers going through cold stores. The insulation and the number of workers are the important variables in the balance of energy and the thermal load calculation (Evans et al, 2014;He et al, 2014;Johnston, 1994). Failure to observe these characteristics compromises the proper functioning of the equipment, causes excessive consumption of energy and compromises the quality of seafood (Johnston, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…The weak correlation observed at the C3 cold store demonstrates that the lower door opening (this cold store is less accessed) does not cause a linear relationship between the period of cold store activities and temperature rise. According to Evans et al, (2014), normal temperature rise occurs because of air flow resulting from doors opening, but several amplitudes are characteristic of food safety errors or equipment malfunction. The temperature increase of frozen and chilled products reduces their shelf life, compromises the original desirable characteristics and encourages spoilage and multiplication of pathogenic microorganisms, thereby increasing the risk of food loss and the occurrence of FBDs (Germano & Germano, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, there is a large difference between the energy use degrees of different cold stores. The specific energy consumptions ranges from 26 to 379 kWh m -3 year -1 are found by literatures [2,3]. Secondly, researches on the energy assessment and energy audit lag behind in the increasing construction of the cold store.…”
Section: Introductionmentioning
confidence: 99%
“…They run on a vapor compressor that is driven by electric or fuel energy, and release amounts of greenhouse gas. It was reported that the cold chain is responsible for approximately 2.5% of global greenhouse gas emissions when considering both direct and indirect effects [2].…”
Section: Introductionmentioning
confidence: 99%